Development Of Macromedia Flash-Based Interactive Media In Food Ingredients Knowledge Subjects - Tresno Ingtyas, Fatma; Akmal, Nikmat (CV. Inara, 2024)
This research aims to develop macromedia flash-based learning media on herbs and spices using the 4 D development model. Research data was collected using a questionnaire that was validated by media experts and material experts. Needs analysis shows that macromedia flash media is really needed by teachers and students. Material expert validation obtained 97.77% in the very feasible category. Media expert validation obtained 89.71% in the very feasible category. The results of students' assessments of the acceptability of Macromedia Flash learning media obtained a score of 4.90, including very high acceptability. Based on these data, it can be concluded that the Macromedia Flash learning media is suitable for use in food ingredient knowledge subjects in Spices and Spices. This media is only limited to knowledge of herbs and spices and quizzes are only provided at the end of the material. It is hoped that future researchers will be able to create quizzes and evaluations on each food ingredient knowledge sub-material and can develop broader material.